2019
DOI: 10.1177/2333393618825253
|View full text |Cite
|
Sign up to set email alerts
|

The Sociocultural Factors Underlying Latina Mothers’ Infant Feeding Practices

Abstract: In this study, we examined the sociocultural factors underlying infant feeding practices. We conducted four focus groups with 19 Latina mothers of children 0 to 2 years of age enrolled in Early Head Start programs in the United States over a 1-year period. We found these mothers considered both science- and family-based feeding recommendations. However, advice from family was often inconsistent with science- and nutrition-based recommended feeding practices. In the interest of showing respect and preserving ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…Overall, the influence of a mother's immediate family on her infant feeding decisions and behaviors reportedly had a strong impact [49,84,85]. Advice from family was often contradictory to nutrition-based feeding guidelines, and to show respect to family members, some mothers incorporated family advice instead of recommended practices [91].…”
Section: Infant Feeding Behaviors Are Influenced By the Socio-culturamentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the influence of a mother's immediate family on her infant feeding decisions and behaviors reportedly had a strong impact [49,84,85]. Advice from family was often contradictory to nutrition-based feeding guidelines, and to show respect to family members, some mothers incorporated family advice instead of recommended practices [91].…”
Section: Infant Feeding Behaviors Are Influenced By the Socio-culturamentioning
confidence: 99%
“…Family, tradition, and culture (social norms within the parent's environment) shaped parental infant feeding beliefs and perceptions about when to begin complementary feeding, and what first foods to offer. Of the studies in this review addressing introduction of solid or semi-solid foods, "beliefs, values, and perceived norms" were a central influence on complementary feeding practices [43,44,49,51,55,59,85,88,89,[91][92][93][94][95][96][97][98][99], which brought challenges to immigrant mothers of children who were culturally separated [100,101]. Parents perceived that "everyone gives you advice" [102], and complementary feeding was viewed as a natural progression with the goal of enjoyment of food and development of an expansive palate [95].…”
Section: Infant Feeding Behaviors Are Influenced By the Socio-culturamentioning
confidence: 99%
“…On the basis of participant responses with probing, mixed feeding (a combination of breastmilk and formula) appears to be common. The reasons given for this practice, such as returning back to work, feeling the baby is still hungry, and feeling like breastmilk production is inadequate, have also been mentioned in previous studies [ 68 - 70 ]. Thus, this work confirms that it will be important to address factors associated with mixed feeding in a future mHealth intervention aimed toward this community and others with similar practices.…”
Section: Discussionmentioning
confidence: 85%
“…It will synthesize this information, along with any relevant information from the current EHS nutrition education program and Phase 1 study findings. Because our pilot work revealed many EHS-enrolled mothers were also enrolled in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), [47] we will also synthesize relevant WIC nutrition education material to ensure intervention components are consistent with WIC messages.…”
Section: Step 1: Intervention Developmentmentioning
confidence: 99%
“…We showed that multiple caregivers, especially grandmothers, are involved in Latinx infant feeding. Although mothers understand the importance of healthy feeding, they may struggle to implement their knowledge in multiple-caregiver infant feeding contexts, increasing the risk for unhealthy infant growth and early childhood obesity [47]. This study addresses these latter concerns first by conducting a longitudinal study to characterize the caregiver context of infant feeding in low-income families and then by developing and testing a version of EHS nutrition programs enhanced by the incorporation of content addressing healthy feeding styles and practices with multiple caregivers.…”
Section: Introductionmentioning
confidence: 99%